Biodiversity of Cephalopod Molluscs and their Accompanying Cartilaginous Fishes in Marine Waters off Latakia Governorate - معروف, رزان (Submission and Review of Research -Biological Sciences Series, 2025)
This research was conducted to update data on the local catch of cephalopod molluscs and associated cartilaginous fishes in the marine water of Latakia governorate. At a time when the Syrian coast suffers from many environmental problems that threaten its bioresources such as population increase, the growth of human activities in various forms, pollution resulting from these activities, and food shortages, in addition to overfishing, and biological invasion by non-native species. Samples of cephalopods and cartilaginous fish were collected monthly from different areas of Latakia coast from May 2023 until April 2024, from depths ranging between 2-60 metres; using different fishing methods and equipment (cages, bottom nets, trawl nets), The samples were classified and morphometric and gravimetric measurements were carried out in the Marine Biology Laboratory at the Higher Institute for Marine Research. The presence of cephalopods and cartilaginous fishes was almost observed in the same fishing nets, in this study, 8 species of cephalopods were and 6 species of cartilaginous fish. It was observed that there was a decline in the number of previously recorded cephalopod species, especially the octopuses that were limited to this research, on Octopus vulgaris. The lack of food was clearly observed through the empty stomachs of most of the samples.